2006
DOI: 10.1111/j.1540-8191.2006.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pannus in the Longevity of an Ionescu-Shiley Pericardial Bioprosthesis

Abstract: As the population ages, bioprosthetic heart valves are increasingly being used to replace diseased native valves. Bioprosthetic valve durability depends on patient age and other factors, but rarely exceeds 15 years. Explanted bioprosthetic valves commonly show tissue degeneration, tears, and calcification. Host tissue overgrowth (pannus), to the extent of interfering with their function, is another finding in bioprostheses that have been in place for long periods. We present a case in which a bovine pericardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
2
0
4
Order By: Relevance
“…On the other hand, this cloth was associated with exuberant pannus overgrowth on ISLP as compared to ISS [26,33]. Butany et al [34] have reported a case in which ISLP valve survived up to 15 years, where pannus had covered the entire stent (both surfaces) and the cusps thus reducing friction and protecting the valve cusp. They also reported a lower incidence of calcification in ISLP, possibly due to antimineralisation treatment [28,29,35] and a lower incidence of infective endocarditis 16% in ISLP as compared to ISS (nearly 50%) reported by others [26,36].…”
Section: Modes Of Failurementioning
confidence: 98%
“…On the other hand, this cloth was associated with exuberant pannus overgrowth on ISLP as compared to ISS [26,33]. Butany et al [34] have reported a case in which ISLP valve survived up to 15 years, where pannus had covered the entire stent (both surfaces) and the cusps thus reducing friction and protecting the valve cusp. They also reported a lower incidence of calcification in ISLP, possibly due to antimineralisation treatment [28,29,35] and a lower incidence of infective endocarditis 16% in ISLP as compared to ISS (nearly 50%) reported by others [26,36].…”
Section: Modes Of Failurementioning
confidence: 98%
“…Операция по замене естественного клапана сердца биопротезом запускает естественную реакцию организма с образованием соединительной ткани по типу рубца на месте иссеченного клапана [7]. Образование соединительно-тканной капсулы является типичной защитной реакцией организма на внедрение инородного тела [8], однако разрастание соединительной ткани (паннуса) зачастую приводит к нежелательным последствиям как для механических [9], так и биологических протезов клапанов сердца [3,10,11]. В составе паннуса определяют коллагеновые волокна, фибронектин и клетки фибробластического типа [10,11].…”
Section: Discussionunclassified
“…Коллагеновые волокна формируют жесткую структуру за счет плотности расположения и отсутствия необходимой извитости. При этом объемное образование паннуса со стороны выводного отдела уменьшает площадь эффективного отверстия клапана, а фиброзная ткань, образованная на поверхности створок, придает дополнительную жесткость створчатому аппарату, снижая его подвижность [3], приводя к перераспределению напряжения на створчатом аппарате. Данные изменения закономерно приводят к повышению давления закрытия (гемодинамическому стрессу) и увеличению градиента давления на клапане [11].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Во время операции по замене естественного клапана сердца биопротезом происходит неизбежная травматизация эндокарда, что, в свою очередь, запускает естественную реакцию организма, конечным результатом которой является образование соединительной ткани по типу рубца на месте иссеченного клапана [7,8]. Однако разрастание соединительной тканиобразование паннуса -зачастую приводит к нежелательным последствиям как для механических [9], так и биологических протезов клапанов сердца [10][11][12][13]. Кроме того, типичной защитной реакцией организма на внедрение инородного тела является образование вокруг него соединительно-тканной капсулы -инкапсуляция.…”
Section: Discussionunclassified